Pore‐formation by adenylate cyclase toxoid activates dendritic cells to prime CD8+ and CD4+ T cells. Issue 4 (1st December 2015) - Svedova, Martina; Masin, Jiri; Fiser, Radovan; Cerny, Ondrej; Tomala, Jakub; Freudenberg, Marina; Tuckova, Ludmila; Kovar, Marek; Dadaglio, Gilles; Adkins, Irena; Sebo, Peter
Abstract : The adenylate cyclase toxin‐hemolysin (CyaA) of Bordetella pertussis is a bi‐functional leukotoxin. It penetrates myeloid phagocytes expressing the complement receptor 3 and delivers into their cytosol its N‐terminal adenylate cyclase enzyme domain ( 400 residues). In parallel, 1300 residue‐long RTX hemolysin moiety of CyaA forms cation‐selective pores and permeabilizes target cell membrane for efflux of cytosolic potassium ions. The non‐enzymatic CyaA‐AC − toxoid, has repeatedly been successfully exploited as an antigen delivery tool for stimulation of adaptive T‐cell immune responses. We show that the pore‐forming activity confers on the CyaA‐AC − toxoid a capacity to trigger Toll‐like receptor and inflammasome signaling‐independent maturation of CD11b‐expressing dendritic cells (DC). The DC maturation‐inducing potency of mutant toxoid variants in vitro reflected their specifically enhanced or reduced pore‐forming activity and K + efflux. The toxoid‐induced in vitro phenotypic maturation of DC involved the activity of mitogen activated protein kinases p38 and JNK and comprised increased expression of maturation markers, interleukin 6, chemokines KC and LIX and granulocyte‐colony‐stimulating factor secretion, prostaglandin E2 production and enhancement of chemotactic migration of DC. Moreover, i.v. injected toxoids induced maturation of splenic DC in function of their cell‐permeabilizing capacity. Similarly, the capacity of DC to stimulate CD8 + and CD4 + T‐cell responses in vitro and in vivo was dependent on the pore‐forming activity of CyaA‐AC − . This reveals a novel self‐adjuvanting capacity of the CyaA‐AC − toxoid that is currently under clinical evaluation as a tool for delivery of immunotherapeutic anti‐cancer CD8 + T‐cell vaccines into DC.